GERMINATION AND EMERGENCE OF FRESH AND AGED SWEET PEPPER (Capsicum anuum L.) SEEDS AS INFLUENCED BY OSMOCONDITIONING TREATMENTS - Beronilla, N.L.; Diputado Jr., M.T. (Annals of Tropical Research, 1997)
Osmoconditioning using polyethylene glycol (PEG) '6000' solution restored the germination capacity of sweet pepper seeds subjected to accelerated ageing treatment to the level of the germination capacity of fresh seeds. It also enhanced uniformity of germination time and speed of germination and seedling emergence of the aged seeds. In fresh seeds, osmoconditioning did not further improve germinatiort percentage but enhanced uniformity and rate of seed germination and seedling emergence. It caused development of taller, more vigorous and heavier seedling in both fresh and aged seeds. The optimum osmotic potential of the PEG solution was -4 bars Pretreatıhent duration of 8 days proved to be more effective than just 4 days.